Latent Profiles of Co-occurring Sexual Problems and Posttraumatic Stress Symptoms Among Young Women Exposed to Sexual Violence - Lipinski, Alexandra J. (Journal of interpersonal violence, 2025)
Sexual dysfunctions (SDs) have been noted to occur following exposure to sexual violence although how these conditions covary with other mental health conditions, particularly posttraumatic stress disorder symptoms (PTSS), is relatively understudied. The current study examined patterns of co-occurring SDs and PTSS in a sample of 328 college-aged, female-identified survivors of adolescent/early adulthood sexual assault (ASA). Latent profile analysis was used to examine patterns of symptom endorsement of various types of SDs and PTSS at the symptom cluster level. Four profiles were identified: asymptomatic (41.2% of sample), sexually distressed + intrusions (24.7%), co-occurring (21%), and PTSS (13.1%). Profiles were compared to one another on various characteristics of sexual assault and social reactions from others following assault disclosure. Results indicated that those in the co-occurring symptom and PTSS profiles reported more severe ASA and more unsupportive social responses relative to the sexually distressed + intrusions and asymptomatic profiles. The asymptomatic profile was significantly less likely to have experienced rape relative to the other three profiles and was less likely to report instances where a close other treated them in a negative manner following assault disclosure. Results are discussed in light of mental health needs for young women who have experienced ASA, with implications discussed for future research and clinical services for university students.